Implementasi Filantropi Islam di Indonesia - Faozan Amar (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2017)
This article discusses the practice of Islamic philanthropy in the Islamic tradition through zakat, infak, alms and waqf. The inherent characteristic of Philanthropy is caring for others, feelings of love to fellow human beings, willingness without coercion to help those in need, both in terms of material and non-material. The foundation is not just because of religious obligations but also the awareness of love and affection for the same human being. Thus, in doing so with lightly selflessness, as well as without regard to differences in race, religion, race and class.